From Agrarian Ritual to Cultural Performance: The Social Representation and Educational Values of Kungkurung Music among the Dayak Meratus - Muhammad Najamudin; Yudi Sukmayadi; Juju Masunah; Tri Karyono; Dedy Ari Nugroho (Journal of Social Work and Science Education, 2026)
This study explores the transformation of Kungkurung music among the Dayak Meratus community in Piani Village, Tapin Regency, South Kalimantan, from its origin as an agrarian ritual toward a contemporary form of cultural performance. Employing a qualitative ethnographic approach, data were collected through participant observation, in-depth interviews, and documentation to reveal the symbolic, social, and pedagogical dimensions of Kungkurung. The findings demonstrate that Kungkurung functions as a medium of collective identity formation and ecological spirituality, reflecting Pierre Bourdieu’s concept of habitus and Merriam’s tripartite framework of music as concept, behavior, and sound. The shift from ritual to public performance exemplifies Jeff Todd Titon’s idea of “continuity in change,” indicating that the community’s adaptation preserves traditional meanings while embracing new socio-cultural contexts. Ethnopedagogically, Kungkurung embodies four educational values collectively, discipline, spirituality, and ecological harmony that sustain intergenerational transmission of cultural wisdom. The study concludes that Kungkurung represents not merely a musical expression but an evolving pedagogical system that integrates art, environment, and social cohesion, thus contributing to cultural sustainability and character education rooted in local wisdom.